Assessment of genetic diversity of different Hyrcanian Boxwood populations for ex situ conservation in Natural Resources Gene Bank of Iran - پروین صالحی شانجانی; حمیده جوادی; لیلا رسول زاده; M. Amirkhani (علوم و فناوری بذر ایران)
Evaluation of necessary and sufficient population number of a species in seed collection program requires knowledge of genetic diversity and differentiation. This study evaluated seed morphology and seed storage proteins profiles of 11 boxwood (Buxus hyrcana) populations, to determine the extent of genetic diversity. Seed morphology and seed storage proteins analysis of variance showed considerable variation with no geographical clines among populations. Hierarchical cluster analysis (UPGMA) of both markers showed that populations sampled from far west (samandkish, Gilan province) and far East (Bandargaz, Glestan province) of Hyrcanian forests were grouped together, however neighbor populations, Namakabrud1 and 2, grouped separately. The results could be due to the phenomenon of fragmentation of boxwood populations. Therefore seed collection from selective populations can lead to the loss of some genes and change genetic structure, indicating the importance of collecting seeds from local ecotypes. In other word seed collection only from a population in each Eco-geoghraphial region is not sufficient and often the populations that located in a same Eco-geoghraphial region may have different genetic structure. These results showed that to avoid genetic erosion of boxwood germplasm, Natural Resources Gene Bank of Iran needs to collect seed from more populations in each Eco-geographical region.